Prawica wobec problemu bezrobocia w Polsce - Aleksandra Ciżmowska (Świat Idei i Polityki, 2001)
Unemployment is one of the most important social and economic problems in Poland in the time of transformation. It became a large-scale phenomenon in the early nineties, when the authority was taken by the parties of the solidarity and opposition origin. During the last years of the Right’s governing the unemployment rate increased again. The article reviews the ideas of counteracting unemployment included into the programs of the rightist and middle-rightist parties playing a significant role in the political life of the country after 1989: the Confederation for Independent Poland, the Christian-Democratic Alliance, the Conservative Peasant Party, the Movement for Poland’s Reconstruction, the Union for Freedom, the Union for Real Politics and the political agreement made by the ”Solidarity” Action for Election. As it results from the performed analysis, most parties assumed intervention of the State into the employment market functioning and pointed to an economic increase as the most important direction of the activities in order to limit unemployment. The specificity of the Polish rightist parties in the nineties was creating programs respecting to a large extend leftist solutions in the social sphere, also including unemployment.